Extinction of Weak Solutions for Nonlinear Parabolic Equations with Nonstandard Growth Conditions (Communications in Mathematical Research, 2021)
This paper deals with the extinction of weak solutions of the initial andboundary value problem for $u_t$ = div$((|u|^σ + d_0)|∇u|^{p(x)−2}∇u)$. When the exponentbelongs to different intervals, the solution has different singularity (vanishing in finitetime).